1993
DOI: 10.1128/mcb.13.5.3103
|View full text |Cite
|
Sign up to set email alerts
|

A developmentally regulated DNA-binding protein from mouse brain stimulates myelin basic protein gene expression.

Abstract: Transcription of the myelin basic protein (MBP) gene is regulated in a cell-type-specific and developmental stage-specific manner during myelin formation in the murine central nervous system. The 5'-flanking region of the MBP gene contains several regulatory elements that differentially contribute to the cell-type-specific transcription of MBP in cells derived from the central nervous system. The proximal element, termed MB1, which is located between nucleotides -14 and -50 with respect to the RNA start site, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
54
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 48 publications
4
54
0
Order By: Relevance
“…This mechanism addresses the initial event whereby a myelin antigen is made available to the immune system. With the recent report of the larger MBP gene (36), interesting studies on transcriptional factors (37) and the possibility that multiple interacting genes may determine susceptibility in MS (38) …”
Section: Discussionmentioning
confidence: 99%
“…This mechanism addresses the initial event whereby a myelin antigen is made available to the immune system. With the recent report of the larger MBP gene (36), interesting studies on transcriptional factors (37) and the possibility that multiple interacting genes may determine susceptibility in MS (38) …”
Section: Discussionmentioning
confidence: 99%
“…Pur␣ is a nearly ubiquitous protein originally purified from mouse brain based on its ability to bind to the DNA fragment containing a GGCGGA sequence derived from the myelin basic protein (MBP) proximal regulatory region (21,22). At that time, human Pur␣ had been identified as a sequencespecific single-stranded DNA-binding protein with a potential role in DNA replication and it had been sequenced (2,3).…”
mentioning
confidence: 99%
“…Several laboratories have demonstrated that relatively small regions of DNA sequence upstream of both the PL P and M BP genes are sufficient for developmental and tissue-specific activation of lacZ expression in oligodendrocytes in transgenic animals (Gow et al, 1992;Goujet-Z alc et al, 1993;Wright et al, 1993;Wrabetz et al, 1995), and transcription factors interacting with these regions have been identified (Berndt et al, 1992;K im and Hudson, 1992;Haas et al, 1993;Wrabetz et al, 1993). Only one of these factors, MyT1, a member of the zinc finger family of DNA-binding proteins, has been shown to be expressed in oligodendrocytes (Armstrong et al, 1995).…”
mentioning
confidence: 99%